Electrocatalytic methanol oxidation with nanoporous gold: microstructure and selectivity. Issue 45 (8th November 2017) - Graf, Matthias; Haensch, Mareike; Carstens, Jörg; Wittstock, Gunther; Weissmüller, Jörg
Abstract : Depending on the synthesis conditions nanoporous gold is found to be an active, selective and durable catalyst for methanol electro-oxidation. Abstract : The properties of Nanoporous Gold (NPG) obtained by the selective dissolution of Ag from an Au–Ag alloy can be tuned by the details of its fabrication, and specifically the residual Ag content is correlated to the ligament size of the material. We link this correlation to methanol electro-oxidation. Specifically, two different NPG types (obtained by potentiostatic dealloying) are compared with one obtained by free corrosion. They show remarkable differences in activity. Quantitative product analysis reveals that NPG shows nearly selective oxidation of CH3 OH to HCOO − when NPG is used as an active electrode in contrast to planar Au. This trend can further be enhanced when applying finer nanoporous structures that are linked to a higher Ag content. X-ray photoelectron spectroscopy (XPS) reveals changes in the nature of residual Ag from which we conclude that Ag is not a passive component in the methanol oxidation process.